2015
DOI: 10.1039/c5cs00082c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning interionic interaction for highly selective in vivo analysis

Abstract: The development of highly selective methodologies to enable in vivo recording of chemical signals is of great importance for studying brain functions and brain activity mapping. However, the complexity of cerebral systems presents a great challenge in the development of chem/(bio)sensors that are capable of directly and selectively recording bioactive molecules involved in brain functions. As one of the most important and popular interactions in nature, interionic interaction constitutes the chemical essence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…So far, a series of EC mircosensors have been rationally tailored for directly monitoring electroactive species employing their inherent physicochemical properties [4] . Nonetheless, EC sensing is subject to insufficient selectivity due to the coexistence of substances with similar properties in the complicated biological system [5] . Moreover, it is still quite challenging to detect electrochemically non‐active species with EC sensors [6] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, a series of EC mircosensors have been rationally tailored for directly monitoring electroactive species employing their inherent physicochemical properties [4] . Nonetheless, EC sensing is subject to insufficient selectivity due to the coexistence of substances with similar properties in the complicated biological system [5] . Moreover, it is still quite challenging to detect electrochemically non‐active species with EC sensors [6] .…”
Section: Methodsmentioning
confidence: 99%
“…[4] Nonetheless, EC sensing is subject to insufficient selectivity due to the coexistence of substances with similar properties in the complicated biological system. [5] Moreover, it is still quite challenging to detect electrochemically non-active species with EC sensors. [6] Another major concern is that the exertion of bias voltage as the excitation source may lead to undesirable electrophysiological stimulation and thus induce non-negligibly abnormal secretion of biomolecules from living systems.…”
mentioning
confidence: 99%
“…In addition to the high sensitivity, selectivity is another key role for the biological sensors. So far, there are several methods to improve the selectivity by rationally designing the surface chemistry of gate electrode (e.g., modifying special materials and/or modulating the interaction of ions (Yu et al, 2015). Liao et al(Figures 6E,F) (Liao et al, 2015), reported a highly selective OECTs-based enzyme sensors.…”
Section: Biological Applications Of Oectsmentioning
confidence: 99%
“…Electrochemical methods have attracted increasing attention monitoring neurochemicals in vivo because selectivity and sensitivity of the methods as well as the anti‐fouling property of the electrode could be principally achieved by rationally designing and constructing electrode/brain interface . By using the online electrochemical system (OECS) developed previously , we herein investigate the effect of lidocaine on the change of Mg 2+ level in IC of guinea pigs following salicylate‐induced tinnitus.…”
Section: Figurementioning
confidence: 99%